Automated Exploratory Data Analysis - Dhillon, Hubble (UMT Artificial Intelligence Review, 2021)
This study introduces a novel framework that can be generalized for an automated exploratory data analysis to test a given hypothesis. The current work is about a drug-related trend and also provides a specific model to test a motivation-related hypothesis in the case of COVID-19. With the utilization of the right, appropriate, and optimized solution available to solve a problem, it is significant that the user feels motivated to delve into the solution for the betterment of society. KEYWORDS: automated exploratory data analysis, motivation-related hypothesis